Manajemen Layanan Perpustakaan Madrasah dalam meningkatkan Minat Baca Peserta Didik di MTs Negeri 10 Jember - Arillia, Icha; Bukhori, Evi Muzaiyidah; Aimmah, Muftiatul (Yayasan Al-Aziziyah Tlogoagung Kedungadem Bojonegoro, 2023)
The purpose of writing this research is to describe the management of library services through mobile libraries at MTsN 10 Jember as strengthening students’ interest in reading, describing the management of madrasa libraries through planning, organizing, implementing, monitoring and evaluating processes. This research uses a descriptive qualitative approach with data collection instruments in the form of observation, interviews and documentation. The subjects of this research were students of MTsN 10 Jember, librarians from the Jember Archives and Library Service. The research results show that Madrasah Library Service Management is something that motivates students to write works entitled Love Poems for My Prophet and Longing for Family Heaven. Apart from the madrasa library, there are other benefits gained from using the mobile library, namely increasing students’ knowledge, insight and abilities, teachers taking an active role in accompanying students, teachers are happy to see students enthusiastic about reading.